Availability, prices and affordability of essential medicines in Haiti - Harinder Singh Chahal; Nazaire St. Fort; Lisa Bero (Journal of Global Health, 2013)
Haiti is the poorest country in the Western Hemisphere and faces numerous challenges, including inadequate medication access for its residents. The objective of this study was to determine the availability, prices, and affordability of essential medicines in Haiti and compare these findings to other countries.